Are we overestimating the negative impact of higher food prices?: Evidence from Ghana - Minot, Nicholas; Dewina, Reno (Wiley, 2015)
Most studies of the welfare impact of higher food prices adopt Deaton's approach, based on the first‐order effect of prices changes using income and expenditure survey data. This paper explores the impact of higher maize and food prices in Ghana and considers the sensitivity of results to changes in several assumptions. If second‐order effects are included, incorporating household response to price changes, the welfare impact of food price increases is more positive, but only modestly so. However, if we assume that marketing margins are constant in real terms rather than proportional to prices, the welfare impact is substantially more positive. These findings highlight the need for more research on the behavior of marketing margins under volatile prices.